AB0453 Do Changes in Clinical Practice Over Time in Europe and Canada Have an Impact on Baseline Characteristics of Patients Initiating Intravenous Abatacept in the Action Study?. (9th June 2015) - Nüβlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H.-M.; Cantagrel, A.; Chartier, M.; Poncet, C.; Rauch, C.; Le Bars, M.
Abstract : Background: Since 2007, IV abatacept has been available in Europe for use in combination with MTX in adults with moderate-to-severe RA failing ≥1 anti-TNF. From 2010 onwards, abatacept was approved for use in patients (pts) failing conventional synthetic (cs)DMARDs (i.e. first-line biologic). In Canada, IV abatacept has been available as mono- or combination therapy for DMARD-failing pts since 2006. An observational study in a single US clinic demonstrated a shift in prescription trends for abatacept over time, towards earlier use in the RA treatment paradigm and in pts with less erosive disease. 1 Objectives: To investigate how the pt population of the real-world ACTION study, in which pts with RA received IV abatacept, has changed over time. Methods: ACTION is a 2-year, international, non-interventional cohort of pts with RA who initiated IV abatacept: Cohort A, enrolled May 2008 to December 2010 (biologic naïve or failed prior biologics [majority]); Cohort B, enrolled September 2010 to December 2013 (biologic naïve only; post-approval in Europe); and Cohort C, enrolled December 2011 to December 2013 (failed prior biologic). Participating countries varied by cohort. Pt characteristics are reported. Categories were compared using the chi-square test, or the Fisher exact test for small pt numbers; scores and other quantitative variables were analysed using the Kruskal–Wallis test. Results: Overall, 2359 pts were enrolled (1137, 553 and 669 in Cohorts A, B and C, respectively); 675 (28.6%) pts were biologic naïve and 1684 (71.4%) had failed prior biologics; 672 and 1671 were included in this analysis, respectively. Pt characteristics for the two cohorts are shown (see Table ). Comparing pts who had failed prior biologics in Cohort A versus Cohort C, those in Cohort C were older, had longer disease duration, were more frequently anti-cyclic citrullinated peptide (anti-CCP) seropositive, more frequently initiated abatacept monotherapy, with a trend for more failed biologic (b)DMARDS, but had lower DAS28 (CRP) and HAQ-DI, and had failed fewer csDMARDS; fewer differences were observed when comparing biologic-naïve pts in Cohort A versus Cohort B, although pts in Cohort B had lower DAS28 (CRP) and were more likely to be anti-CCP seropositive. The proportions of pts with co-morbidities were similar across the cohorts. Conclusions: In this real-world setting, differences over time between enrolment cohorts of pts with RA receiving IV abatacept reflect the changes in clinical practice. Over time, lower pt baseline DAS28 (CRP) and HAQ-DI indicate improved access to biologics for pts with less active disease; more pts with anti-CCP seropositivity indicates increased treatment of pts with poor prognostic factors; more pts failing ≥3 bDMARDs despite awareness of the acceptable safety profile of abatacept across all treatment lines reflects access to an increasing range of biologics. References: Schiff M, et al. Int J Clin Rheumatol 2010;5:581–91. Disclosure of Interest: H. Nüβlein Consultant for: Bristol-Myers Squibb, Abbvie, Chugai, UCB, Wyeth, Pfizer, MSD, Novartis and Roche, Speakers bureau: Bristol-Myers Squibb, Abbvie, Chugai, UCB, Wyeth, Pfizer, MSD, Novartis and Roche, R. Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, M. Galeazzi: None declared, H.-M. Lorenz Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, A. Cantagrel Grant/research support from: Pfizer, UCB, Roche, Chugai, Speakers bureau: Bristol-Myers Squibb, Pfizer, Chugai, Abbvie, Nordic-Pharma, Fabre, MSD, Novartis, M. Chartier Consultant for: Bristol-Myers Squibb, C. Poncet Consultant for: Bristol-Myers Squibb, Employee of: DOCS, C. Rauch Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb